Pelatihan Praktikum Sains untuk Siswa Sanggar Sentul Kuala Lumpur Malaysia - Dewi, Novi Ratna; Listiaji, Prasetyo; Linuwih, Suharto; Priatmoko, Sigit; Amalia, Andin Vita; Stephani Diah Pamelasari (Universitas Negeri Semarang, 2024)
Every Indonesian citizen is blessed to receive a proper education, including the children of migrant workers abroad. Until now, there has not been much attention to education for the children of migrant workers. Sanggar Sentul Kuala Lumpur exists as a forum to facilitate non-formal education for the children of migrant workers in Kuala Lumpur and its surroundings. The non-formal education carried out at Sanggar Sentul has certainly not run optimally due to several limitations such as infrastructure, the relatively diverse age range of children, and the lack of a systematic curriculum being implemented. One of the learning activities that is rarely carried out is practicum in science subjects considering that there are not yet adequate practicum facilities there. Based on these problems, the community service team of Universitas Negeri Semarang carried out practical science training for students at Sanggar Sentul in an effort to improve the quality of learning for the children of migrant workers who attend school there. The activity was carried out by training studio students in three simple experiments: the Archimedes experiment, making buildings from straws, and making lava lamps. The students were very enthusiastic about participating in the practicum. Apart from that, this activity also received a very good assessment from students.